Recent Advances in Real-Time Musical Effects, Synthesis, and Virtual Analog Models. (28th February 2011) - Pakarinen Pakarinen, Jyri Jyri; Välimäki Välimäki, Vesa Vesa; Fontana Fontana, Federico Federico; Lazzarini Lazzarini, Victor Victor; Abel Abel, Jonathan S. Jonathan S.
Abstract : This paper reviews some of the recent advances in real-time musical effects processing and synthesis. The main emphasis is on virtual analog modeling, specifically digital emulation of vintage delay and reverberation effects, tube amplifiers, and voltage-controlled filters. Additionally, adaptive effects algorithms and sound synthesis and processing languages are discussed.